Comparative Genomic and Transcriptomic Analysis Suggests the Evolutionary Dynamic of GH3 Genes in Gramineae Crops - Kong, Weilong; Zhang, Yue; Deng, Xiaoxiao; Li, Shuangmiao; Zhang, Chenhao; Li, Yangsheng (Frontiers in Plant Science, 2019)
Glycoside hydrolase 3 (GH3) gene family belongs to auxin-responsive gene families and is tightly linked with hormone homeostasis and signaling pathways. However, our knowledge about the evolutionary dynamic of GH3 genes in Gramineae crops is limited. In this study, a comparative genomic and transcriptomic analysis was conducted to study evolutionary patterns and the driving selective forces of GH3 gene family in six representative Gramineae crops, namely, Setaria italica (Si), Zea mays (Zm), Sorghum bicolor (Sb), Hordeum vulgare (Hv), Brachypodium distachyon (Bd), and Oryza sativa ssp. japonica (Os). A total of 17, 13, 11, 9, 8, and 11 GH3 proteins (GH3s) were identified in Si, Zm, Sb, Hv, Bd, and Os, respectively. Phylogenetic, conserved motif, and gene structural analyses could divide all GH3s into two groups (I and II), and all GH3s consisted of seven orthogroups (Ors) on the basis of Or identification result. We further found that genes in the same Or showed similar sequence and structural features, whereas genes in the same groups exhibited intrinsic differences in exon numbers and intron lengths. These results revealed GH3 genes in the same groups have been differentiated. Obvious differences in total numbers of GH3 genes, Ors, and duplication events among these six tested Gramineae crops reflected lineage-specific expansions and homologous gene loss/gain of GH3 gene family during the evolutionary process. In addition, selective force and expression analyses indicated that all GH3 genes were constrained by strong purifying selection, and GH3 genes in conserved Ors showed higher expression levels than that in unconserved Ors. The current study highlighted different evolutionary patterns of GH3 genes in Gramineae crops resulted from different evolutionary rates and duplication events and provided a vital insight into the functional divergence of GH3 genes.